Sterilisasi Komersial Cassava Chunk pada Kemasan Hermetis Standing Pouch dan Perubahan Sifat Fisikokimianya - Dewi Sartika Saragih; Dede Robiatul Adawiyah; Fransisca Zakaria Rungkat (Jurnal Ilmu Pertanian Indonesia, 2021)
People’s lifestyles nowdays tend to want healthy-practical food that is strongly supported by a healthy diet. Cassava as whole food is considered as a healthy food and has the potential to become rice substitute but needs an appropriate technology to facilitate food serving. In this research, ready-to-eat cassava products then called "cassava chunk" were made by applying canning technology using retort pouch packaging. The achieved value of the heat adequacy (F0) is very important in the canning process to ensure food safety. Therefore, this study aimed to produce cassava chunk product as a whole food, optimize the size and amount of brine in the sterilization process, determine the F0 value after blanching and non-blanching treatments, as well as to analyze the chemical characteristics of fresh cassava and cassava chunk. The sterilization was done by using a pressure cooker with a specially designed basket using hermetic retort pouch packaging. The initial characterizations showed that fresh cassava had a pH of 6.70 and 0.9 aw at 24.6°C. The addition of 20% (b/v) 1% brine solution in the sterilization process with 3 x 2.5 cm cassava chunk was the most preferred by the panelists. The sterilization process with blanching treatment before being packaged reached an F0 of 3.43 minutes, which was safe to consume, and with non-blanching treatment before being packaged reached an F0 of 2.73 minutes. The proximate analysis of cassava chunk showed an increase in the water content from 60.89% to 68.44%, the starch content increased from 74.43% to 80.41%, the soluble dietary fiber decreased from 6.78% to 3.34%, but the fat content decreased from 1.54% to 0.65%. Meanwhile, ash, protein, and insoluble dietary fiber did not show any significant differences after the sterilization. Sterilization technology could produce ready-to-eat cassava chunk as a whole food and was acceptable by 45 organoleptic panelists. Keywords: cassava chunk, whole food, proximate analysis, F0